THE IMPLEMENTATION OF ONLINE DISPUTE RESOLUTION IN INDONESIA’S DIGITAL ECONOMIC SECTOR (CASE STUDY: TOKOPEDIA) - Hutagalung, Angela Yohanna (UNES Law Review, 2023)
Online Dispute Resolution (ODR) is a form of Alternative Dispute Resolution (APS) with the help of electronic media. This research provides a thorough analysis of the implementation of ODR in disputes that occur in the digital economy sector with a case study of Tokopedia. This research is also supported by a review of regulations and literature related to the legal issues that the author examines. Regarding the implementation and existence of Online Dispute Resolution in Indonesia, there is no specific regulation that specifically regulates it. However, the existence of Law Number 11 of 2008 on Electronic Information and Transactions as amended by Law Number 19 of 2016 ("ITE Law"), Government Regulation Number 80 of 2019 on Trading Through Electronic Systems ("PPE-Commerce"), Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution ("Arbitratrion and ADR Law") can be said to be sufficient to support the validity of ODR mechanisms and decisions. Looking at digital developments, special arrangements for ODR in an electronic or online-based transaction have become urgent at this time. This is due to the potential disputes that may arise in daily transactions.